CD146 is closely associated with the prognosis and molecular features of osteosarcoma: Guidance for personalized clinical treatment - Wang, Jingkun; Wu, Zhonghan; Zheng, Meige; Yu, Shuisheng; Zhang, Xin; Xu, XinZhong (Frontiers in Genetics, 2022)
Background: Osteosarcoma (OSA) is one of the focuses for orthopedic surgeons, always with severe death due to metastasis. CD146 is severely expressed in several tumors, indicating its potential as a biomarker for OSA. Method: Two OSA cohorts were enrolled in this study. The Therapeutically Applicable Research to Generate Effective Treatments-Osteosarcoma (TARGET-OS) cohort was used as a training cohort, and GSE21257 was used as the external validation cohort. The R package ‘limma’ was used to discriminate the differentially expressed genes among CD146-high and CD146-low patients and was further annotated by the enriched signaling pathways. The R package “MOVICS” was used to evaluate immune infiltration and the response to chemotherapy and immunotherapy. All statistical analyses were performed by R version 4.0.2, and P < 0.05 was considered statistically significant. Result: CD146 plays an important role in promoting the progression, invasion and metastasis of several tumors. In the current study, we first revealed an integrative unfavorable prognosis in patients with tumors (P < 0.01, HR: 1.10, 95% CI: 1.07-1.14). CD146 is tightly correlated with m5C RNA methylation modification genes in OSA. Furthermore, we revealed that CD146 acts as an oncogene in OSA patients and is linked to poor prognosis in both the TARGET-OS cohort (P = 0.019, HR: 2.61, 95% CI: 1.171-5.834) and the GSE21257 cohort (P = 0.005, HR: 3.61, 95% CI: 1.474-8.855), with a total of 137 patients, regardless of whether they were adjusted for clinical pathological features. Highly expressed CD146 impacts the signaling pathways of cytokine‒cytokine receptor interactions and is associated with the high infiltration of immunocytes. Moreover, patients with high CD146 expression were more likely to be sensitive to anti-PD-1 immunotherapy, while patients with low expression of CD146 were more likely to be sensitive to cisplatin and doxorubicin chemotherapy. Conclusions: Overall, CD146 is an independent prognostic factor for OSA patients and can help doctors select clinical treatment strategies.